Adenomatous polyposis coli and a cytogenetic deletion of chromosome 5 resulting from a maternal intrachromosomal insertion. Issue 4 (April 1994) - Barber, J C; Ellis, K H; Bowles, L V; Delhanty, J D; Ede, R F; Male, B M; Eccles, D M
Abstract : We present the clinical and laboratory findings in an institutionalised adult patient originally referred for autism. A high risk of colorectal cancer was predicted when an interstitial deletion of the long arm of chromosome 5, del(5)(q15q22.3), was detected in her lymphocytes and deletion of the MCC and APC genes confirmed by molecular analysis. Adenomatous polyposis coli and carcinoma of the rectum were subsequently diagnosed in the patient. She was profoundly mentally retarded, autistic, and had minor dysmorphic features consistent with those of previous patients with similar deletions. The deletion arose as a result of recombination within the small insertion loop formed at meiosis by the direct insertion (dir ins(5)(q22.3q14.2q15)) found in the patient's mother. This family further confirms the cytogenetic mapping of both MCC and APC genes to 5q22 and comparison with other recent cases suggests that both genes and their closely linked markers lie within the 5q22.1 subband.